2022
DOI: 10.1186/s12913-022-08136-6
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by edentulous patients (EDPs) during complete denture prostheses (CDP) service delivery in Fiji – a qualitative study

Abstract: Background Edentulism is a state of having no teeth in the oral cavity, an irreversible condition popularly known as the marker of disease burden on the oral health. For edentulous patients (EDPs) Complete Denture Prostheses (CDP) is a means to improve oral health. Due to limited studies in this area, this research aimed to explore the challenges faced by the EDPs during CDP service delivery in Fiji. Methods A directed descriptive qualitative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…9 BioMed Research International Some EDPs had reported that they had very less to no knowledge on the CDP they had received from their dentists on how to clean and maintain their CDP as well. Similar sentiments were highlighted by Nand M. and Mohammadnezhad M., Berteretche, M. V. et al, and Sjogren, P. et al stating patients were not informed about CDP care and maintenance which led to lack of oral hygiene and poor perception of denture care in EDPs [21,35,36].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…9 BioMed Research International Some EDPs had reported that they had very less to no knowledge on the CDP they had received from their dentists on how to clean and maintain their CDP as well. Similar sentiments were highlighted by Nand M. and Mohammadnezhad M., Berteretche, M. V. et al, and Sjogren, P. et al stating patients were not informed about CDP care and maintenance which led to lack of oral hygiene and poor perception of denture care in EDPs [21,35,36].…”
Section: Discussionsupporting
confidence: 59%
“…There has never been a prior study done on CDP where patients and DPs like the dentists and dental technicians' perceptions were studied. There are a few previous studies on complete denture wearers [ 17 , 19 , 20 ] that had been conducted where the complaints based on care and maintenance of dentures and challenges of EDPs were elaborated [ 21 ]. This limited availability of information for a country like Fiji warrants for further research to be undertaken in this area which is essential in the lives of both the EDPs and the DPs in terms of exploring the perception of the EDPs and DPs towards the extent of care and maintenance given to their CDP in Fiji.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that wearing ill-tting or uncomfortable complete dentures can have undesirable effects on the denture-supporting tissues, hence the oral health of the patient [29][30]. Additionally, several studies have revealed different levels of experiences regarding the rehabilitation of edentulous patients which include the occurrence of blisters, di culty in closing the mouth and loose dentures, painful gums, food lodgment, and unstable mandibular complete dentures as well as loss of retention and mucosal irritation [31][32][33][34]. However, no published study has explored the lived experiences with RCDs among the Ugandan population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it affects both oral and general health [1,[7][8][9][10]. Although the prevalence of total edentulism has decreased over the last decade, data from the World Health Organization (WHO) and independent studies in 42 countries show that the prevalence of total edentulism is the lowest in Nigeria (1.3%) and the highest in Bosnia-Herzegovina (78%) among those aged >65 years [1,4,5,[11][12][13][14][15]. Few studies have examined the prevalence of total edentulism in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%